Microclimas e áreas verdes na cidade de Fortaleza - CE - Branco, Kauberg Gomes Castelo (2014)
With the consolidation of Fortaleza as a major urban center in the ninth century and XX, and with the creation of its metropolitan region in the 1970s, is observed intensification in urban density and therefore a disclosure of city environmental problems, including those related to urban climate . In this perspective it was proposed to investigate, following the methodology of the Urban Climate System of Monteiro (1976, 2003), the climate in intra-urban areas of Fortaleza, specifically the green spaces and surroundings, aiming to analyze the thermal contrasts these areas with the gifted environments of construction. Samples were collected on representative days of contrasting seasonal periods, as follows: Autumn (on 25 and 26 April 2013), winter (27 and 28 August 2013), and the dry season with intense winds and Finally, in days (21 and 22 November 2013). Through the methodology proposed by Bargos, 2010, categorizing, spatial in Public Areas Green and potentially public. The description of each green area of ​​the city were also held. Consideration was also the green area per inhabitant Index (IAV), as territorial scale opted for Regional later cauculando She administered the distribution of green areas in the city as a whole. As a result, Fortaleza has somo result of Green Areas Mapping the total of 13.34 m² / h (Public green areas) and 1.88 m² / h (Green Area Public Potentially). We observed the variation in temperature significantly intra-urban environment in general. The inner points thermal amplitudes were lower than the external points, the latter being more warm in the four sample areas analyzed.